Estabilidad de fenitoína sódica en polvo contenida en cápsulas dosificada en el hospital “Belén” de Trujillo” - Agurto Sánchez, Alicia (2009)
In the present work the stability of sodium Fenitoína in dust contained in capsules dosed in the hospital was determined “Bethlehem” of Trujillo. The present concentrations of Sodium Fenitoína in the reformulations in the form of dust were determined, in time zero, 7.14 and 24 days, these concentrations were comparing the areas of the Standard and the samples obtained by means of the analysis by Liquid Hight Chromatography Resolution (HPLC). According to the obtained results one concludes that the period of validity of the Sodium Fenitoína - Medifarma Laboratory, in dust contained in capsules dosed in the Hospital “Bethlehem” of Trujillo, is 20 days and that its stability is not altered in this period under normal environmental conditions of temperature and humidity. In addition the kinetic ones to degradation to realise the studies of stability of the Sodium Fenitoína are of order zero and one.